SEXUALITY IN A CONTEXT OF SPECULATIVE POSTHUMANISM: HUMAN-POSTHUMAN RUPTURES AND DISCONNECTIONS - Zahurska, Nataliia V. (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2019)
In this article human-posthuman ruptures and disconnections both in comprehension and in practices, as well as the possibility of epistemological contingency contemporaneously are investigated. This means that an epistemological ruptures and an ontological disconnections of sexuality both differ from one another, and also join together. Since ancient times both sensitive and sensible practices of sexuality were considered the best mode to concern to sexual care of self. It has shown that, in relation to sexuality, a correlation of epistemological discontinuity and continuity is possible. Sexuality, which is actualized with the help of both natural, vital and death, annihilative drives, fits into the context of onticology as a posthuman ontology. Being connected with the thermodynamics of infinitesimal vital parts, anonymous strange strangers, singularities, it turns out to be especially awesome. Such a mode of sexuality is not necessarily reproductive; rather, it unfolds in the fluid space of non-presence and at the same time determines this space. It emphasizes that that the cos mo‑illogical becoming of posthuman leads to negentropy or extropy as vitality. Following this position, the foucaultian conception of the care of self mirrors lacanian graphs of sexuation in a context of object-oriented ontologies in comparison with philosophies of presence. It is recognized that this is the sexuality of the productive disconnection and the pleasure cosmic dissolution. This article concludes by illustrating that the mode of sexuality of Speculative Posthumanism is contingent with the Libidinal Materialism or Vital Posthumanism in a context in which the sexuality of Wide Human Descendants (WHDs) is thought to be oriented to that which is pleasure and is differentiated.